On covering distant minterms by the camp algorithm - Biswas, N.N. (IEEE transactions on computer-aided design of integrated circuits and systems, 1990)
The computer-aided minimization procedure (CAMP) algorithm is a minterm-based computer-aided procedure for the minimization of single Boolean functions. Major modifications of the algorithm are presented. They allow it always to obtain the minimum cover covering all the uncovered minterms, both adjacent and distant, in the normal mode. In the branch mode, the solution may not be minimum in many cases. However, a new theorem introduced in the algorithm allows it to switch to the branch mode only when it is inevitable. The improved algorithm also has a mechanism which ensures the largest possible dimension for each cube of the solution.< >